How does Subantarctic Mode Water ventilate the Southern Hemisphere subtropics?. Issue 9 (5th September 2016) - Jones, Daniel C.; Meijers, Andrew J. S.; Shuckburgh, Emily; Sallée, Jean‐Baptiste; Haynes, Peter; McAufield, Ewa K.; Mazloff, Matthew R.
Abstract: In several regions north of the Antarctic Circumpolar Current (ACC), deep wintertime convection refreshes pools of weakly stratified subsurface water collectively referred to as Subantarctic Mode Water (SAMW). SAMW ventilates the subtropical thermocline on decadal timescales, providing nutrients for low‐latitude productivity and potentially trapping anthropogenic carbon in the deep ocean interior for centuries. In this work, we investigate the spatial structure and timescales of mode water export and associated thermocline ventilation. We use passive tracers in an eddy‐permitting, observationally‐informed Southern Ocean model to identify the pathways followed by mode waters between their formation regions and the areas where they first enter the subtropics. We find that the pathways followed by the mode water tracers are largely set by the mean geostrophic circulation. Export from the Indian and Central Pacific mode water pools is primarily driven by large‐scale gyre circulation, whereas export from the Australian and Atlantic pools is heavily influenced by the ACC. Export from the Eastern Pacific mode water pool is driven by a combination of deep boundary currents and subtropical gyre circulation. More than 50% of each mode water tracer reaches the subtropical thermocline within 50 years, with significant variability between pools. The Eastern Pacific pathway is especially efficient, with roughly 80% entering the subtropical thermocline within 50 years. The time required for 50% of the mode water tracers to leave the Southern Ocean domain varies significantly between mode water pools, from 9 years for the Indian mode water pool to roughly 40 years for the Central Pacific mode water pool. Key Points: The export of Subantarctic Mode Water into the subtropical thermocline displays significant regional variability Export pathways display the relative influence of the subtropical gyres and ACC The Eastern Pacific pathway is an especially efficient mode water export route due to boundary current transport